How to assess capacity to make a will. Issue 7611 (19th July 2007) - Jacoby, Robin; Steer, Peter
Abstract : Much litigation in the United Kingdom and elsewhere could be avoided if doctors correctly assessed the capacity of a person to make a will. An old age psychiatrist and a solicitor explain how to assess capacity using legal tests